The Effects of Acute and Chronic Psychological Stress on Bladder Function in a Rodent Model - Smith, Ariana L.; Leung, Joanne; Kun, Suny; Zhang, Rong; Karagiannides, Iordanes; Raz, Shlomo; Lee, Una; Golovatscka, Viktoriya; Pothoulakis, Charalabos; Bradesi, Sylvie; Mayer, Emeran A.; Rodríguez, Larissa V. (Urology (Ridgewood, N.J.), 2011)
Psychological stress plays a role in the exacerbation of functional lower urinary tract disorders, such as painful bladder syndrome and overactive bladder. To better understand the mechanism underlying this relationship, we characterized changes in micturition, anxiety-related behavior, and bladder pathology in rats exposed to repeated water avoidance (WA) stress. Twenty-four Wistar rats were subjected to WA stress or sham. Immediately after acute (day 1) and chronic (day 10) stress or sham, rats were placed in a metabolic cage for a 2-hour voiding behavior assessment. Voiding parameters were compared with baseline values obtained before stress. Four animals from each group were sacrificed on day 10 and bladders harvested for histologic and gene expression studies. The remaining 8 animals per group underwent repeated voiding assessment every 3 days for 1 month followed by 10 days of repeat WA stress or sham. Bladder histology and gene expression were studied. Rats exposed to WA stress developed a significant increase in micturition frequency and decrease in latency to void, voiding interval, and volume of first void compared with sham and baseline. Alterations in micturition persisted for approximately 1 month. Stressed rats showed increased fecal pellet excretion and anxiety-like behavior. In addition, bladder specimens from stressed animals revealed increased angiogenesis, and increased total and activated mast cells. In rats, repeated psychological stress results in lasting alterations in micturition frequency, interval, and volume. This rodent model may represent a valid tool for studying syndromes characterized by increased urinary frequency.